PERAN KELUARGA TERHADAP PENDIDIKAN ISLAMI DI PAUD QURRATUL A’YUN KAMPAR - Kusmiran, Kusmiran; Hitami, Munzir; Yusuf, Kadar M (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
This research is to determine the role of the family in the perspective of Islamic education in PAUD Qurratul A'yun Kampar. This study uses a quantitative descriptive method. The results showed that: 1) Family understanding of religious education: 20 respondents, 80% stated that religious education at an early age was important, while 20% said it was not important, 2) parents graduated from junior high school as much as 10%, high school graduates as much as 25% , 55% of bachelor's graduates and 10% of master's graduates, and 3) Worship Education: 90% of parents teach prayers, memorizing short letters, reading iqra', 5% of parents call private teachers and the other 5% rely on education from schools .